Efeito do desvanecimento Nakagami-m na escalabilidade das redes LoRa/LoRaWAN - Honório, Felipe Gonsalez (2018)
In the context of Internet of Things (IoT), this work studies the scalability of LoRa/ LoRaWAN wireless sensor networks in fading environments. To that end, we employ computer simulations in order to look at the effect of the wireless fading modeled by a Nakagami-m distribution on the maximum number of nodes that can be placed in a given region, constrained to a minimal data extraction rate compatible with typical IoT applications. The results show that the scalability of the LoRa network decreases considerably, with the number of devices reduced from 3 to 6% for the Nakagami-m channel with m = 2, characteristic of line-of-sight scenarios, and of 9 to 18% in Nakagamim channels with m = 1, equivalent to the Rayleigh channel without line-of-sight, compared to the AWGN channel. In addition, it has been shown that there is an optimal spreading factor (SF) that depends on the network node density and duty cycle. With smaller SFs it is observed that the amount of errors due to fading losses is dominant in the total amount of errors, representing more than 86% of packet loss cases. However, when the SF increases, the robustness of the receiver also increases, consequently reducing the probability of error in function of the fading. On the other hand, the number of collisions begins to become significant, since the propagation time of each symbol increases with the SF.